Ecosystem Metabolism Modulates the Dynamics of Hypoxia and Acidification Across Temperate Coastal Habitat Types - Wallace, Ryan B.; Peterson, Bradley J.; Gobler, Christopher J. (Frontiers in Marine Science, 2021)
Changes in photosynthetic and respiration rates in coastal marine habitats cause considerable variability in ecosystem metabolism on timescales ranging from diel to tidal to seasonal. Here, temporal and spatial dynamics of dissolved oxygen (DO), carbonate chemistry, and net ecosystem metabolism (NEM) were quantified from spring through fall in multiple, distinct, temperate estuarine habitats: seagrass meadows, salt marshes, an open water estuary, and a shallow water habitat dominated by benthic macroalgae. DO and pHT (total scale) measurements were made via high frequency sensor arrays coupled with discrete measurements of dissolved inorganic carbon (DIC) and high-resolution spatial mapping was used to document intra-habitat spatial variability. All habitats displayed clear diurnal patterns of pHT and DO that were stronger than tidal signals, with minimums and maximums observed during early morning and afternoon, respectively. Diel ranges in pHT and DO varied by site. In seagrass meadows and the open estuarine site, pHT ranged 7.8–8.4 and 7.5–8.2, respectively, while DO exceeded hypoxic thresholds and aragonite was typically saturated (ΩAr > 1). Conversely, pHT in a shallow macroalgal and salt marsh dominated habitats exhibited strong diel oscillations in pHT (6.9–8.4) with diel acidic (pHT < 7) and hypoxic (DO < 3 mg L–1) conditions often observed during summer along with extended periods of aragonite undersaturation (ΩAr < 1). The partial pressure of carbon dioxide (pCO2) exceeded 3000 and 2000 μatm in the salt marsh and macroalgal bed, respectively, while pCO2 never exceeded 1000 μatm in the seagrass and open estuarine site. Mesoscale (50–100 m) spatial variability was observed across sites with the lowest pHT and DO found within regions of more restricted flow. NEM across habitats ranged from net autotrophic (macroalgae and seagrass) to metabolically balanced (open water) and net heterotrophic (salt marsh). Each habitat exhibited distinct buffering capacities, varying seasonally, and modulated by adjacent biological activity and variations in total alkalinity (TA) and DIC. As future predicted declines in pH and DO are likely to shrink the spatial extent of estuarine refuges from acidification and hypoxia, efforts are required to expand seagrass meadows and the aquaculture of macroalgae to maximize their ecosystem benefits and maintain these estuarine refuges.